1999
DOI: 10.1159/000007590
|View full text |Cite
|
Sign up to set email alerts
|

Differential Distribution of Serotonin and Tryptophan Hydroxylase in the Human Gastrointestinal Tract

Abstract: The distribution of tryptophan hydroxylase, the rate-limiting enzyme in the biosynthesis of serotonin, was investigated immunohistochemically in various organs of the gastrointestinal tract and compared with that of neuroendocrine markers. While immunoreactivity for serotonin and chromogranin A was restricted to enterochromaffin cells, positive staining for tryptophan hydroxylase was detected in normal enterocytes lining the epithelium of the small intestine. Tryptophan hydroxylase was localized in the supranu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 16 publications
(30 reference statements)
2
16
0
3
Order By: Relevance
“…Similar to our results, the differentiated villous epithelial cells displayed an intense immunoreactivity for anti-TPH antibody in the human duodenum. 34 Consistently, we found observations suggesting subtle 5-HT synthesis in Caco-2 cells. SP, a BH4 precursor, increases cellular BH4 levels much more effectively than BH4 itself when used as the supplement.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to our results, the differentiated villous epithelial cells displayed an intense immunoreactivity for anti-TPH antibody in the human duodenum. 34 Consistently, we found observations suggesting subtle 5-HT synthesis in Caco-2 cells. SP, a BH4 precursor, increases cellular BH4 levels much more effectively than BH4 itself when used as the supplement.…”
Section: Discussionsupporting
confidence: 86%
“…Other hormones are also present in the gastrointestinal tract including melatonin [51] and serotonin [52]; both are neural hormones which maintain homeostasis and both reduce chlamydial infection [53]. In addition, plants use indole 3-acetic acid as their main hormone (for cell growth, division, tissue differentiation, and response to light and gravity), and bacteria interrupt this eucaryotic signaling by using indole-3-acetic acid as a source of carbon, nitrogen, and energy [54].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether the adrenal gland-cortex or medulla-can synthesize 5-HT. In the human, TPH was not detected immunohistochemically in the adrenal cortex (Meyer and Brinck 1999). An interesting connection between adrenal gland and brain 5-HT synthesis was made by Miller et al (1980), who demonstrated that brain tryptophan utilization was determined by the presence or absence of the adrenal gland.…”
Section: E 5-hydroxytryptamine Presence and Function In The Adrenal mentioning
confidence: 99%